The Effect of Vitamin D Supplementation on Clinical Outcomes for Critically Ill Patients: A Systemic Review and Meta-Analysis of Randomized Clinical Trials - Shen, Hejuan; Mei, Yijun; Zhang, Kai; Xu, Xiaoya (Frontiers in Nutrition, 2021)
Purpose: Vitamin D deficiency is common in critically ill patients, and was proved to be associated with worse outcomes. However, the effect of vitamin D supplementation for critically ill patients remains controversial. Thus, we conducted a meta-analysis to evaluate the effect of vitamin D supplementation among critically ill patients. Methods: Electronic databases PubMed, Embase, Scopus, and the Cochrane Library were searched for eligible randomized controlled trials up to January 2021. The primary outcome was overall mortality, and secondary outcomes were length of intensive care unit stay, length of hospital stay, duration of mechanical ventilation. Subgroup analyses were performed to explore the treatment effect by type of admission, route of administration, dose of supplemented vitamin D, and the degree of vitamin D deficiency. Results: A total of 14 studies involving 2,324 patients were finally included. No effect on overall mortality was found between vitamin D supplementation and control group (OR 0.73, 95%CI 0.52 to 1.03, I2=28%). The vitamin D supplementation reduced the length of intensive care unit stay (MD -2.25, 95%CI -4.07 to -0.44, I2=71%) and duration of mechanical ventilation (MD -3.47, 95%CI -6.37 to -0.57, I2=88%). In the subgroup analyses, the vitamin D supplementation for surgical patients (OR 0.67, 95%CI 0.47 to 0.94, I2=0%) or through parenteral way (OR 0.42, 95%CI 0.22 to 0.82, I2=0%) was associated with reduced mortality. Conclusion: In critically ill patients, the administration of vitamin D as compared to placebo has no effect on overall mortality but might decrease the length of intensive care unit stay and duration of mechanical ventilation. Further trials are needed to confirm our findings.